Microwave-Assisted Extraction and Phytochemical Profile of Nonea pulmonarioides and Its Antifungal, Antibacterial, and Antioxidant Activities - Haval H. Mohammed; Fuad O. Abdullah (Journal of Food Quality)
Microwave-assisted extraction (MAE) was chosen to isolate secondary natural compounds from Nonea pulmonarioides. MAE is an efficient approach compared to maceration. In our study of N. pulmonarioides, the Folin–Ciocalteu and trichloroaluminum techniques were used to determine the total phenolic and flavonoid contents. Antioxidant activity was determined by the β-carotene/linoleic acid test. The minimum inhibitory concentration (MIC) was measured using the microwell dilution assay method. Overall, MAE may represent a substantially faster extraction system (5 min) with an even greater extraction yield than maceration extraction (24 h). Phytochemical screening indicated the existence of classes of several secondary metabolites. The methanol extract had a high total phenolic content (TPC) of 113.33 ± 1.06 μg of gallic acid equivalents (GAE)/mg of dry plant weight, while the total flavonoid content (TFC) in the acetone extract was 44.26 ± 0.88 μg of quercetin equivalent (QE)/mg of the dry plant. The antioxidant activity data correlated well with the acetone extract (32.41 ± 0.93, I%) compared to the other extracts. The antimicrobial assay (MIC) results showed high activity of the extract against Candida albicans for the petroleum ether extract, which was significantly higher than against other microorganisms. The quantitative gas chromatography-mass spectrophotometry (GC-MS) analysis of the extracts confirmed that the most abundant compound in the methanol extract was ethyl tridecanoate (45.94%), while nonadecane was the predominant compound in the acetone (35.7%) and the petroleum ether (18.34%) extracts.